2021
DOI: 10.1094/pbiomes-11-19-0064-fi
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation and Resorption Efficiency Differences Among Twelve Upland and Lowland Switchgrass Cultivars

Abstract: In nitrogen (N)-limited terrestrial ecosystems, plants employ various strategies to acquire and conserve N, including translocation of N in perennial tissues and stimulation of N fixation in roots and soils. Switchgrass (Panicum virgatum) is a genotypically and phenotypically diverse perennial grass with two distinct ecotypes (lowland and upland) and numerous genotypes. It grows well in low-N soils, likely because of its ability to translocate N and to associate with N-fixing microbes, but little is known abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…Roley et. al [26] determined that N resorption efficiencies averaged 53% for lowland versus 29 % for upland switchgrass cultivars. Aerts [22] indicated that the N-RE and P-RE differed among evergreen shrubs and trees, deciduous shrubs and trees, graminoids and forbs, and also varied by sites.…”
Section: Discussionmentioning
confidence: 99%
“…Roley et. al [26] determined that N resorption efficiencies averaged 53% for lowland versus 29 % for upland switchgrass cultivars. Aerts [22] indicated that the N-RE and P-RE differed among evergreen shrubs and trees, deciduous shrubs and trees, graminoids and forbs, and also varied by sites.…”
Section: Discussionmentioning
confidence: 99%
“…Future research and breeding efforts will likely discover multiple selection criteria within holobiont consortia, as diverse microbiota have both complementary and competitive influences on the hologenome (Theis et al., 2016). By considering the influence of AM fungi, among the most widespread symbiotic partners in both natural and agroecosystems, our work sets a baseline for further study involving additional mutualistic microbes such as nitrogen‐fixing bacteria (Roley et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Mycorrhizal symbioses are widespread and typically beneficial, suggesting that evaluation of mycorrhizal relationships is critical groundwork for disentangling additional plant-associated microbial dynamics of the total holobiont. For example, switchgrass breeders are also assessing the influence of nitrogen-fixing bacteria on switchgrass growth in low-N soils (Rodrigues et al, 2017;Roley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen is one of the most common limiting nutrients for crops and switchgrass response to nitrogen fertilizer has been variable (Casler, 2021; Casler et al, 2019; Fike et al, 2017). These variable results could be due to the naturally high nutrient efficiency of the crop, residual soil nutrients, or associative nitrogen fixation (Lemus et al, 2008; Roley et al, 2021; Yang et al, 2016; Yost et al, 2017). This uncertainty is challenging for a breeding program.…”
Section: Introductionmentioning
confidence: 99%